Oldest Immiscible Silica‐rich Melt on the Moon Recorded in a ~4.38 Ga Zircon. Issue 4 (18th February 2020) - Zeng, Xiaojia; Joy, Katherine H.; Li, Shijie; Lin, Yangting; Wang, Nian; Li, Xiongyao; Li, Yang; Hao, Jialong; Liu, Jianzhong; Wang, Shijie
Abstract: The temporal duration of lunar‐evolved magmatism is still poorly constrained. In lunar meteorite Northwest Africa (NWA) 10049, a melt inclusion‐bearing zircon fragment provides a new tool to understand the composition and age of the melts from which zircon directly crystallized. The studied zircon‐hosted melt inclusions are silica rich and iron poor (e.g., ~80–90 wt% SiO2 ; <0.5 wt% FeO), compositionally similar with immiscible silica‐rich melts found in Apollo rocks. Nano‐SIMS U–Pb analyses of the zircon yielded a minimum crystallization age of 4, 382 ± 40 Ma, older than the ages for Apollo highly evolved alkali suite lithologies (~3.8–4.33 Ga). Our study shows that the melt inclusion‐bearing zircon in NWA 10049 is the oldest microscale evidence for documenting immiscible silica‐rich melts in lunar samples, suggesting that lunar‐evolved silica‐rich melts were prevalent as early as ~4.38 Ga. This work implies that there would be a prolonged silicic magmatism occurred on the Moon. Plain Language Summary: Lunar‐evolved silica‐rich melt is thought to be related to the formation of highly silicic lithologies (e.g., granitic lithologies). These rock types have been observed in Apollo returned samples as lithic clasts and also have been detected by remote‐sensing data as silicic domes. The Apollo‐evolved lithologies give a wide range of crystallization ages from ~3.8–4.33 Ga. However, there is still unclear about the temporal duration of lunar‐evolved magmatism and volcanism. In lunar meteorite breccia NWA 10049, a melt inclusions‐bearing zircon fragment provides a new tool to understand the composition and age of the melts from which zircon directly crystallized. The studied zircon‐hosted melt inclusions are compositionally similar with immiscible silica‐rich melts found in Apollo rocks. Nano‐SIMS U–Pb analyses of the zircon yielded a minimum crystallization age of ~4.38 Ga. This age is older than the ages for Apollo‐returned granites (up to 4.33 Ga) and ancient basaltic volcanism (i.e., up to ~4.37 Ga), making the studied zircon is the oldest microscale evidence for documenting lunar silicate liquid immiscibility. Key Points: A ~200‐μm‐sized melt inclusion‐bearing zircon fragment was found in lunar feldspathic breccia meteorite NWA 10049 Melt inclusions in this zircon are compositionally consistent with lunar immiscible silica‐rich melts The zircon is 4.38 Ga and provides microscale evidence for ancient immiscible silica‐rich melt on the Moon